Improvement of retinal tissue perfusion after circuit resistance training in healthy older adults - Zhang, Juan; Strand, Keri; Totillo, Matthew; Chen, Qi; Signorile, Joseph F.; Jiang, Hong; Wang, Jianhua (Experimental gerontology, 2021)
To determine the retinal tissue perfusion (RTP) and its relation to cognitive function in healthy older people after an 8-week high-speed circuit resistance training program (HSCT). Eleven subjects in the HSCT group and seven age-matched non-training controls (CON) were recruited. The HSCT group trained 3 times per week for 8 weeks, while CON performed no formal training. One eye of each subject in both groups was imaged at baseline and at an 8-week follow-up, using a Retinal Function Imager to measure retinal blood flow (RBF). Retinal tissue perfusion (RTP) was calculated as RBF divided by the corresponding tissue volume. Cognitive function was assessed during both visits using the NIH Toolbox Fluid Cognition Battery. RTP was 2.99 ± 0.91 nl·s−1·mm−3 (mean ± SD) at baseline and significantly increased to 3.77 ± 0.86 nl·s−1·mm−3 after training (P < 0.001) in the HSCT group, reflecting an increase of 26%. In the HSCT group, the Pattern Comparison Processing Speed Test (PAT) and Fluid Cognition Composite Score (FCS) were significantly increased after HSCT (P = 0.01). Furthermore, the changes in Flanker Inhibitory Control and Attention Test (FLNK) were positively correlated to increases in RTP (r = 0.80, P = 0.003). This is the first prospective study to demonstrate that the increased RTP after HSCT was related to improved cognition in cognitively-normal elders, indicating RTP could be an imaging marker for monitoring cognitive changes due to physical activity in the elderly.